(untitled) (Third Sector Social Economic Review, 2025)
Okun’s law is a fundamental macroeconomic principle that reveals the negative relationship between the unemployment rate and economic growth. This study aims to analyze the validity of Okun’s law using general, male, and female unemployment rates covering the period from 2005:Q1 to 2024:Q2 in the Turkish economy, along with Gross Domestic Product (GDP) variables calculated using the production, income, and expenditure methods. Within the methodological framework of the analysis, the Fractional Frequency Fourier ADF (FFFADF) unit root test was first applied to the variables, and then the validity of Okun’s law between each GDP variable and each unemployment rate was examined separately using Wavelet Transform Coherence (WTC) analysis. The analysis results provided strong evidence that Okun’s law is generally applicable in Türkiye. It has been determined that the relationship is most valid for GDP calculated by the production method, and least valid for the female unemployment rate. More pronounced negative relationships were observed between the male unemployment rate and GDP. These results show that growth and employment dynamics differ depending on the method of calculating GDP and the type of unemployment. In light of the findings, while the role of policies supporting economic growth in reducing unemployment is confirmed, it is emphasized that employment policies, particularly those targeting the male labor force, can have a more pronounced positive impact on GDP, and these dynamics should be considered in policy design.